PERTANGGUNGJAWABAN NEGARA DAN PENANGANAN SAMPAH RUANG ANGKASA (SPACE DEBRIS) MENURUT HUKUM INTERNASIONAL - Megah Adi Pramana, Ida Bagus Gede; Maharta Yasa, Made (Kertha Desa; Vol 10 No 6 (2022), 2022)
The number of space activities carried out by countries causes more space debris and will harm the earth's ecosystem and space. This article aims to find out how the international arrangements for countries' responsibilities for the existence of space debris and what can be done to overcome space debris. The research in this article uses normative research methods that use a statutory approach. This article results, where according to the international legal instruments used in the space debris problem, countries must be responsible for damage caused by the launch of space objects. Such responsibilities can based on mistakes made by the launch countries. Efforts to overcome space debris are by creating recommendation and guidline mechanisms used by countries and space agencies in the implementation of space activities. However, it is necessary to establish an international environmental tribunal to address court proceedings that cannot be effectively conducted by existing courts.